Differential Expression of MARK4 Protein and Related Perturbations in Females with Ovulatory PCOS - Fazilat, Ahmad; Rashid, Nadia; Nigam, Aruna; Anjum, Shadab; Gupta, Nimisha; Wajid, Saima (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Ovulatory PCOS (OPCOS) is the mildest form of the polycystic ovarian syndrome among all four determined phenotypes. Though the females with OPCOS are ovulating, hyperandrogenism and polycystic ovarian morphology increase the susceptibility of cardiovascular diseases, insulin resistance, hyperlipidemia and metabolic syndrome in these females. Objectives: The aim of the study was to identify the significance associated with OPCOS phenotype through serum proteomic profiling of OPCOS females and normal age-matched healthy ovulating females. Methods: One and two-dimensional gel-based proteomic approaches were adopted to fractionate the complex serum proteome. Differential protein profiles generated were analyzed with PD-QUEST Software. Protein spots differing in intensity by >2-fold were selected and identified further by MALDI-TOF MS. Validation of identified protein was carried out by Biolayer Interferometry. Results: One and two-dimensional gel profiles revealed a differential expression pattern of proteins. 10 selected spots were identified as GMP synthase [glutamine hydrolyzing], zinc finger protein 518A, pericentriolar material 1 protein, BCLAF1 and THRAP3 family member 3, MAP/microtubule affinityregulating kinase 4, H/ACA ribonucleoprotein complex subunit 1, Melanoma-associated antigen B3 and Zinc finger protein 658B. Expression of MAP/microtubule affinity-regulating kinase 4 (MARK4) was found to be downregulated in OPCOS females as compared to controls on validation. Conclusion: Reduced expression of MARK4 protein in OPCOS increases the associated risk of hyperlipidemia, hyperandrogenism and metabolic syndrome, thus the protein holds strong candidature as a drug target for the syndrome.
Keywords: hyperlipidemia